An Overview of the Current Scientific Evidence on the Biological Properties of Abelmoschus esculentus (L.) Moench (Okra) - Carsten Tsun-Ka Kwok; Yam-Fung Ng; Hei-Tung Lydia Chan; Shun-Wan Chan (Foods)
Abelmoschus esculentus (L.) Moench, commonly known as okra or lady’s finger, is an annual flowering plant belonging to the Malvaceae family. Okra is a native plant in Africa as well as a traditional medicine in Africa and India for treating different diseases and conditions. Today, okra is widely consumed as a vegetable and is increasingly recognized as a superfood due to its rich nutritional profile and potential pharmacological benefits. Research indicates that okra exhibits a range of biological activities, including antidiabetic, antihyperlipidemic, antifatigue, vasoprotective, hepatoprotective, antitumor, anti-inflammatory, and antimicrobial effects. Despite its promising therapeutic potential, research on the active compounds in okra and evaluating efficacy in clinical settings remains limited. This review aims to consolidate existing scientific knowledge on the biological and pharmacological properties of okra, thereby encouraging further investigation into its health benefits. Ultimately, this could pave the way for the development of functional foods or health supplements that leverage okra as a key ingredient to prevent chronic diseases and enhance overall health outcomes.